The associations of phthalate biomarkers during pregnancy with later glycemia and lipid profiles. (October 2021) - Wu, Haotian; Just, Allan C.; Colicino, Elena; Calafat, Antonia M.; Oken, Emily; Braun, Joseph M.; McRae, Nia; Cantoral, Alejandra; Pantic, Ivan; Pizano-Zárate, María Luisa; Tolentino, Mary Cruz; Wright, Robert O.; et al.
Highlights: Phthalate mixture at pregnancy was associated with long-term insulin resistance. Phthalate mixture at pregnancy was associated with long term adverse lipid profiles. Associations with glycemia biomarkers were primarily driven by MECPTP and ∑DBP. Associations with lipid biomarkers were primarily driven by MECPTP, ∑DBP, and MEP. Pregnancy phthalates exposure may be associated with long-term metabolic health. Abstract: Background: Pregnancy induces numerous cardiovascular and metabolic changes. Alterations in these sensitive processes may precipitate long-term post-delivery health consequences. Studies have reported associations between phthalates and metabolic complications of pregnancy, but no study has investigated metabolic outcomes beyond pregnancy. Objectives: To examine associations of exposure to phthalates during pregnancy with post-delivery metabolic health. Design: We quantified 15 urinary phthalate biomarker concentrations during the second and third trimesters among 618 pregnant women from Mexico City. Maternal metabolic health biomarkers included fasting blood measures of glycemia [glucose, insulin, Homeostatic Model Assessment of Insulin Resistance [HOMA-IR], % hemoglobin A1c (HbA1c%)] and lipids (total, high-density lipoprotein (HDL), low-density lipoprotein (LDL) cholesterol, triglycerides), at 4–5 and 6–8 years post-delivery. To estimate the influence of the phthalates mixture, we used Bayesian weighted quantile sum regression and Bayesian kernel machine regression; for individual biomarkers, we used linear mixed models. Results: As a mixture, higher urinary phthalate biomarker concentrations during pregnancy were associated with post-delivery concentrations of plasma glucose (interquartile range [IQR] difference: 0.13 SD, 95%CrI: 0.05, 0.20), plasma insulin (IQR difference: 0.06 SD, 95%CrI: −0.02, 0.14), HOMA-IR (IQR difference: 0.08 SD, 95% CrI: 0.01, 0.16), and HbA1c% (IQR difference: 0.15 SD, 95%CrI: 0.05, 0.24). Associations were primarily driven by mono-2-ethyl-5-carboxypentyl terephthalate (MECPTP) and the sum of dibutyl phthalate biomarkers (∑DBP). The phthalates mixture was associated with lower HDL (IQR difference: −0.08 SD, 95%CrI: −0.16, −0.01), driven by ∑DBP and monoethyl phthalate (MEP), and higher triglyceride levels (IQR difference: 0.15 SD, 95%CrI: 0.08, 0.22), driven by MECPTP and MEP. The overall mixture was not associated with total cholesterol and LDL. However, ∑DBP and MEP were associated with lower and higher total cholesterol, respectively, and MECPTP and ∑DBP were associated with lower LDL. Conclusions: Phthalate exposure during pregnancy is associated with adverse long-term changes in maternal metabolic health. A better understanding of timing of the exact biological changes and their implications on metabolic disease risk is needed.